2016
DOI: 10.1212/wnl.0000000000002369
|View full text |Cite
|
Sign up to set email alerts
|

Vascular factors in suspected normal pressure hydrocephalus

Abstract: Objective: We examined clinical and imaging findings of suspected idiopathic normal pressure hydrocephalus (iNPH) in relation to vascular risk factors and white matter lesions (WMLs), using a nested case-control design in a representative, population-based sample.Methods: From a population-based sample, 1,235 persons aged 70 years or older were examined with CT of the brain between 1986 and 2000. We identified 55 persons with hydrocephalic ventricular enlargement, i.e., radiologic findings consistent with iNPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 43 publications
4
69
1
4
Order By: Relevance
“…Thus, an association between cardiovascular disease and idiopathic normal pressure hydrocephalus (iNPH) was suggested (Casmiro et al., 1989; Earnest, Fahn, Karp, & Rowland, 1974; Edwards, Dombrowski, Luciano, & Pople, 2004; Graff‐Radford & Godersky, 1987; Jaraj et al., 2016; Koto, Rosenberg, Zingesser, Horoupian, & Katzman, 1977; Krauss et al., 1996). More recently, an increased age‐adjusted prevalence of cardiovascular disease and diabetes was reported in iNPH (Eide & Pripp, 2014) and noncommunicating hydrocephalus (ncHC) (Eide & Pripp, 2016) as compared to the general population (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an association between cardiovascular disease and idiopathic normal pressure hydrocephalus (iNPH) was suggested (Casmiro et al., 1989; Earnest, Fahn, Karp, & Rowland, 1974; Edwards, Dombrowski, Luciano, & Pople, 2004; Graff‐Radford & Godersky, 1987; Jaraj et al., 2016; Koto, Rosenberg, Zingesser, Horoupian, & Katzman, 1977; Krauss et al., 1996). More recently, an increased age‐adjusted prevalence of cardiovascular disease and diabetes was reported in iNPH (Eide & Pripp, 2014) and noncommunicating hydrocephalus (ncHC) (Eide & Pripp, 2016) as compared to the general population (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…13,39 The prevalence of this disease is age related, reaching 1%-5.9% among elderly individuals. 21,26 It remains one of the most controversial neuropathological entities both in regards to its diagnosis and its proper management. Characteristically, despite many recent advances in imaging methods, most NPH cases still remain idiopathic.…”
mentioning
confidence: 99%
“…The exact underlying pathophysiological mechanism of this disorder has remained ill defined, and several theories supporting the combination of CSF circulation disturbances along with other cerebrovascular disorders have been proposed. 1,21,28,36,41,58 The diagnosis of NPH is based on a patient's clinical status, imaging findings, and the natural history of the disease. The imaging criteria for NPH are mainly ventricular enlargement (i.e., with an Evans index > 0.3), lack of any anatomical obstruction of the CSF circulation, enlarged temporal horns, and a corpus callosum (CC) angle of greater than 40° on brain CT or MRI scans.…”
mentioning
confidence: 99%
“…8,9 In studies of vascular risk factors in patients with iNPH, the risk factors alone, such as diabetes or hypertension, do not seem to have a negative impact on outcome after shunting. 8,9 In studies of vascular risk factors in patients with iNPH, the risk factors alone, such as diabetes or hypertension, do not seem to have a negative impact on outcome after shunting.…”
Section: Vascular Comorbidity and Shunt Surgerymentioning
confidence: 99%
“…4 Whether or not these outcome rates hold for older patients is not fully clarified; there are reports that high age could be a negative predictor for shunt surgery outcome, 5 while more recent reports propose that age alone should not exclude patients from surgery. 8,9 Earlier studies have reported that vascular comorbidities are associated with a less favourable outcome, [10][11][12] while more recent studies report that vascular disease is not a negative predictor. 8,9 Earlier studies have reported that vascular comorbidities are associated with a less favourable outcome, [10][11][12] while more recent studies report that vascular disease is not a negative predictor.…”
Section: Introductionmentioning
confidence: 99%